POLA MANAJEMEN KOMUNIKASI INTERPERSONAL GURU BIMBINGAN KONSELING DALAM MENANGANI PELANGGARAN KEDISIPLINAN PADA SISWA - Deden Ramdan (Linimasa : Jurnal Ilmu Komunikasi, 2023)
ABSTRACT The research entitled "Patterns of Interpersonal Communication of Counseling Teachers in Handling Disciplinary Violations in Students". This study has a discussion of how interpersonal communication patterns that occur between counseling teachers and students in dealing with disciplinary violations. Which is analyzed using symbolic interaction theory from Herbert Blumer which has five concepts, namely the self-concept, the act concept, the object concept, the social interaction concept, and the joint action concept. The purpose of this research was to find out how the communication patterns are carried out by counseling teachers who focus on interpersonal communication that occurs in guidance counseling teachers and students in dealing with disciplinary violations at SMP Ignatius Slamet Riyadi. The research method used by researchers in this study is a qualitative method with a qualitative descriptive study approach. Data collection was carried out through field observations and interviews, as well as documentation. There were twenty two people as informants, including one expert informant, one academic informant, and twenty students as supporting informants. The results of this study indicate that the communication that occurs between guidance and counseling teachers and students is formed from self-concepts that are built by each individual and act based on the meaning of each of them. Guidance and counseling teachers and students understand each other's objects, so that from the interactions that occur between the guidance and counseling teachers and students, joint action can be obtained between the guidance and counseling teachers and students in dealing with disciplinary violations.